Adenosine receptors in cutaneous thermal hyperemia and active vasodilation in humans - Fieger, Sarah M. (Kansas State University, 2011)
Mechanisms underlying the cutaneous vasodilation response to local skin heating and whole body heating in humans remain unresolved. Although nitric oxide (NO) is known to contribute to these responses, it remains unclear as to the source of NO. Adenosine receptors induce vasodilation in many human tissues and may work, in part, through NO. As these receptors are also known to be located in the cutaneous vasculature, the studies contained in this thesis were designed to investigate a potential contribution of adenosine receptor activation to the rise in skin blood flow elicited by local skin and whole body heating. The study presented in chapter IV was designed to determine a potential role for adenosine receptors in contributing to cutaneous thermal hyperemia. Four cutaneous microdialysis sites were randomly assigned one of four drug treatments designed to elucidate the contribution of A[subscript]1/A[subscript]2 adenosine receptors during local skin heating. Each site was locally heated from a baseline temperature of 33°C to 42°C at a rate of 1°C/10 s and skin blood flow was monitored via laser-Doppler flowmetry (LDF). The data obtained from these experiments suggest A[subscript]1/A[subscript]2 adenosine receptor activation directly contributes to cutaneous thermal hyperemia. These data further suggest a portion of the NO response may be explained by A[subscript]1/A[subscript]2 adenosine receptor activation; however, a substantial portion of the NO response is independent of the adenosine receptor contribution. The study presented in chapter V was designed to determine a potential role for A[subscript]1/A[subscript]2 adenosine receptors in contributing to cutaneous active vasodilation. Four cutaneous microdialysis sites were randomly assigned one of four drug treatments, as above, and skin blood flow was monitored via LDF. Whole body heat stress, sufficient to raise oral temperature at least 0.8°C above baseline, was induced via water-perfused suits. The data obtained from these experiments suggest A[subscript]1/A[subscript]2 adenosine receptor activation does not directly contribute to cutaneous active vasodilation; however, a role for A[subscript]1/A[subscript]2 adenosine receptor activation is unmasked when NO synthase is inhibited. The data from this study further suggest that A[subscript]1/A[subscript]2 adenosine receptor activation may be responsible for a portion of the known NO component of cutaneous active vasodilation.
Keywords: Skin; Blood Flow; Adenosine receptors; Kinesiology (0575)